Unconventional U.S. monetary policy: New tools, same channels? - Martin Feldkircher; Florian Huber (Journal of Risk and Financial Management, 2018)
In this paper, we compare the transmission of a conventional monetary policy shock with that of an unexpected decrease in the term spread, which mirrors quantitative easing. Employing a time-varying vector autoregression with stochastic volatility, our results are two-fold: First, the spread shock works mainly through a boost to consumer wealth growth, while a conventional monetary policy shock affects real output growth via a broad credit/bank lending channel. Second, both shocks exhibit a distinct pattern over our sample period. More specifically, we find small output effects of a conventional monetary policy shock during the period of the global financial crisis and stronger effects in its aftermath. This might imply that when the central bank has left the policy rate unaltered for an extended period of time, a policy surprise might boost output particularly strongly. By contrast, the spread shock has affected output growth most strongly during the period of the global financial crisis and less so thereafter. This might point to diminishing effects of large-scale asset purchase programs.
Keywords: C32; E52; E32; 330; unconventional monetary policy; transmission channel; Bayesian TVP-SV-VAR; Geldpolitische Transmission; Quantitative Lockerung; Schock; Wirkungsanalyse; Verbraucherpreisindex; Bruttoinlandsprodukt; VAR-Modell; Bayes-Statistik; USA